The Early Palaeozoic mega‐thrusting of the Gondwana‐derived Altay–Lake zone in western Mongolia: Implications for the development of the Central Asian Orogenic Belt and Paleo‐Asian Ocean evolution. (6th February 2020) - Khukhuudei, Ulambadrakh; Kusky, Timothy; Otgonbayar, Orolzodmaa; Wang, Lu
Abstract : The position of structures of Mongolia during Rodinia break‐up and Paleo‐Asian Ocean opening is debatable, and reconstructions between them are poorly known. In this paper, we apply an integrated approach to the not widely known yet distinctive structure (ribbon‐like) of the Lake and Mongolian Altay zones in western Mongolia, relating these with the surrounding Tuva–Mongolian and central Mongolian microcontinents (CMMs) development within the Central Asian Orogenic Belt (CAOB) and Paleo‐Asian Ocean evolution. We present a summary of the Neoproterozoic–early Palaeozoic tectonic development of western Mongolia and the CAOB and suggest a new comprehensive model for its evolution. The Lake zone of Mongolia is a major zone of ophiolite and arc complexes within the CAOB. The main sections of ophiolites are located along the west margin, bordering with Precambrian crystalline basement of the CMM. The ophiolites are distributed from north to south and have been dated to have similar ages. A classic oceanic plate stratigraphy section is preserved in the Lake zone. Serpentinite mélange and other volcanogenic‐terrigenous assemblages from the Lake zone are characterized by a system of nappe sheets thrust over the Dzavkhan block of the CMM. The ribbon‐like structure that the southern part of the Altay–Lake zone preserves at present provides an explanation for the development between the Gondwana‐derived microcontinent and Paleo‐Asian Ocean. During the pre‐Neoproterozoic, convergence accretion between Siberia and the CMM formed the Tuva–Mongolian belt, which later converted to the Altay–Lake collision zone associated with the thrusting of its eastern margin. All well‐known ophiolites of western Mongolia (Agardag, Khantayshir, and Dariv) as well as ophiolites of the Erdene Uul area mostly correspond to an "open‐ocean" phase with drifting microcontinents between 655 and 540 Ma or Neoproterozoic. In the early Neoproterozoic, the Altay peninsula‐like ribbon microcontinent after rifting of East Gondwana gradually drifted to Siberia. In this time, the east margin of the Paleo‐Asian Ocean was developed as a passive margin with the Dzavkhan Block. The Paleo‐Asian ocean plate simultaneously drifted to the CMM, whereas the Altay microcontinent moved into Siberia‐CMM. In middle‐upper Neoproterozoic times, the eastern part of the Paleo‐Asian ocean plate was thrusted over the CMM, obducting ophiolites (e.g., Tas Khairkhan), in the early Cambrian time, an oceanic spreading centre (?) of the Paleo‐Asian Ocean reached the CMM and stopped obduction. In the Neoproterozoic, the west margin of the Paleo‐Asian Ocean was developed as an active continental margin, with subduction under the Gondwana‐derived microcontinent. In the early Cambrian, there was significant subduction rollback and accretion of seamounts (Turgen). Later, in middle Cambrian–early Ordovician times, a large turbidite sequence was deposited in Altay. During the Devonian to Carboniferous, the Paleo‐Asian Ocean was preserved as a remnant ocean or big sea (Lake zone), accumulating marine deposits after collision of Siberia and the Altay microcontinent by late Cambrian.